Local search metaheuristics for Capacitated Vehicle Routing Problem: a comparative study - Sergey Mikchailovitch Avdochin; Ekaterina Nikolaevna Beresneva (Труды Института системного программирования РАН, 2019)
This study is concerned with local search metaheuristics for solving Capacitated Vehicle Routing Problem (CVRP). In this problem the optimal design of routes for a fleet of vehicles with a limited capacity to serve a set of customers must be found. The problem is NP-hard, therefore heuristic algorithms which provide near-optimal polynomial-time solutions are still actual. This experimental analysis is a continue of previous research on construction heuristics for CVRP. It was investigated before that Clarke and Wright Savings (CWS) heuristic is the best among constructive algorithms except for a few instances with geometric type of clients’ distribution where Nearest Neighbor (NN) heuristic is better. The aim of this work is to make a comparison of best-known local search metaheuristics by criteria of error rate and running time with CWS or NN as initial algorithms because there were not found any such state-of-the-art comparative study. An experimental comparison is made using 8 datasets from well-known library because it is interesting to analyze “effectiveness” of algorithms depending on type of input data. Overall, five different groups of Pareto optimal algorithms are defined and described.